Analisis Teologis mengenai Kejatuhan Manusia dalam Kejadian 3 dan Anugerah Allah melalui Pemulihan Nya - Rikias Gulo; Malik Bambangan (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
This article examines the narrative of human fall in Genesis chapter 3 and the manifestation of God's grace within it. Using qualitative and hermeneutical methods, this research analyzes how the disobedience of Adam and Eve brought universal consequences for humanity. This fall not only resulted in the breakdown of the relationship between humans and God but also brought consequences in the form of curses and suffering. However, in the midst of this tragedy, God showed His grace through the promise of salvation in Genesis 3:15 and the provision of animal skin clothing as a symbol of His care. This promise was later fulfilled through the coming of Jesus Christ who defeated the power of sin. This article also emphasizes the relevance of the story of human fall for today's life, especially in understanding the importance of maintaining integrity in relationship with God and appreciating the grace of salvation that has been given through Christ.